Identification of LncRNAs Associated With FOLFOX Chemoresistance in mCRC and Construction of a Predictive Model - Zhang, Yiyi; Xu, Meifang; Sun, Yanwu; Chen, Ying; Chi, Pan; Xu, Zongbin; Lu, Xingrong (Frontiers in Cell and Developmental Biology, 2021)
FOLFOX regimen is the first-line chemotherapy of patients with metastatic colorectal cancer (mCRC). However, studies are limited regarding lncRNAs associated with FOLFOX chemotherapy response and prognosis. This study aimed to identify lncRNAs associated with FOLFOX chemotherapy response and prognosis in mCRC patients and to construct a predictive model. We analyzed lncRNA expression in 11 mCRC patients treated with FOLFOX chemotherapy before surgery (4 sensitive, 7 resistant) by Gene Array Chip. The top eight lncRNAs (AC007193.8, CTD-2008N3.1, FLJ36777, RP11-509J21.4, RP3-508I15.20, LOC100130950, RP5-1042K10.13, and LINC00476) for chemotherapy response were identified according to the Weighted correlation network analysis (WGCNA). A ceRNA network was then constructed. The crucial functions of the eight lncRNAs enriched in chemotherapy-resistance were MAPK and proteoglycans signaling pathway. ROC analysis demonstrated that the eight lncRNAs were effective predictors for chemotherapy resistance of mCRC patients. To further identify a signature model lncRNA chemotherapy response and prognostic, the validation set consisted of 196 CRC patients from our center was used to validate lncRNAs expression and prognosis by qPCR. The result demonstrated that the expression of the eight lncRNAs expression between CRC cancerous and adjacent non-cancerous tissues was also verified in the validation data set to determine the prognostic value. A generalized linear model was established to predict the probability of chemotherapy resistance and survival. Our findings showed that the eight-lncRNA signature may be a novel biomarker for the prediction of FOLFOX chemotherapy response and prognosis of mCRC patients.